2008
DOI: 10.1128/jvi.00238-08
|View full text |Cite
|
Sign up to set email alerts
|

Double-Stranded RNA Adenosine Deaminases Enhance Expression of Human Immunodeficiency Virus Type 1 Proteins

Abstract: ADARs (adenosine deaminases that act on double-stranded RNA) are RNA editing enzymes that catalyze a change from adenosine to inosine, which is then recognized as guanosine by translational machinery. We demonstrate here that overexpression of ADARs but not of an ADAR mutant lacking editing activity could upregulate human immunodeficiency virus type 1 (HIV-1) structural protein expression and viral production. Knockdown of ADAR1 by RNA silencing inhibited HIV-1 production. Viral RNA harvested from transfected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
104
4
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(113 citation statements)
references
References 35 publications
4
104
4
1
Order By: Relevance
“…4C and 5D). A similar activity was recently observed in an independent study and showed that the deaminase function was responsible for this increased HIV production (45). However, we observed similar results with our Dcat mutant and ADAR1-p150 in the absence of PKR, which does not support the same conclusion (Fig.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…4C and 5D). A similar activity was recently observed in an independent study and showed that the deaminase function was responsible for this increased HIV production (45). However, we observed similar results with our Dcat mutant and ADAR1-p150 in the absence of PKR, which does not support the same conclusion (Fig.…”
Section: Discussioncontrasting
confidence: 56%
“…It was suggested recently that the overexpression of ADAR1 or ADAR2, another member of the ADAR family, increases HIV production in the absence of PKR transfection, and this activity was ascribed to the deaminase function (45). To determine if this was also the case in our assay, we verified the activity of our constructs in the absence of transfected PKR (Fig.…”
Section: Vol 83 2009 Adar1 Inhibition Of Pkr During Hiv Infection 1mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, with vesicular stomatitis virus, ADAR1 was found to be proviral in both mouse embryonic fibroblasts and HeLa cells by suppressing the activation of PKR phosphorylation (25,34). Several independent reports concluded that ADAR1 was proviral and increased HIV replication (11,14,40). Furthermore, in a screening of ϳ380 ISGs by overexpression, ADAR1 was identified as one of a few ISG products that significantly enhanced the replication of multiple viruses, including HIV, West Nile virus, Venezuelan equine encephalitis virus, and yellow fever virus (50).…”
Section: Discussionmentioning
confidence: 96%
“…Thus, TREX1 serves to hide HIV from the innate immune system. ADAR1 was reported to promote HIV replication [69,70]; however, anti-retroviral effects of ADAR1 were demonstrated in a recent study [71]. SAMHD1 potently suppresses HIV replication in noncycling human cells by degrading dNTPs and reducing their concentration below a threshold required for viral reverse transcription [25,26,[72][73][74].…”
Section: A Unifying Concept Of Ags Pathogenesis?mentioning
confidence: 99%